Α new species, Bryobia attica (Acari: Tetranychidae) from Greece - Hatzinikolis Ε.Ν.; Emmanouel, N.G. (ENTOMOLOGIA HELLENICA, 1990)
The adult female and larva of Bryobia attics n. sp. are described and illustrated. It was collected from Olea europaea bark in Kessariani and Koropi regions of Attiki, Greece.